Institutional Groundings for Transformative Work with Students and in Schools - Kevin Michael Foster (Universidade Federal de Juiz de Fora, 2016)
Despite local, state and federal funding for compulsory education, educational opportunity is not evenly distributed in the United States. A range of challenges disproportionately face students of color and the poor and lead to uneven achievement outcomes. This essay uses the example of a specific universitybased institute to show how partnerships between universities, schools and communities can improve the likelihood of academic success among minority and impoverished populations. It further discusses an emergent theory of practice that can guide universitybased action-researchers who would hope to harness the resources of the academy and build partnerships that affect sustainable improvements in education. The article discusses purposefully constructing a seamless harmony between teaching, research and service among university faculty in order to facilitate research that directly and positively impacts local communities, generates knowledge, and facilitates the training and development of graduate students. It also argues that community-engaged work with underserved student and family populations includes both contextual and structural dimensions, and that careful attention to both may be necessary for achieving structural transformations that ensure that all students will be served well by their schools.